A COMPARATIVE ANALYSIS OF BLOOM’S TAXONOMY IN LEARNING OUTCOMES OF 10TH-GRADE MERDEKA CURRICULUM MODULES IN YOGYAKARTA AND WEST KALIMANTAN - Gabriela Apriani Koli; Prisca Eirene Pricillia; Melvina Risky Gabriella; Caku Caku; Concilianus Laos Mbato (Journal of English Educational Study (JEES), 2026)
The Merdeka Curriculum gives schools and teachers greater autonomy in designing ‘result learning objectives’, which can result in variations in cognitive orientation between regions. This study examines the distribution of LOTS and HOTS in the learning outcomes of 10th grade English classes developed based on the Merdeka Curriculum in two regional contexts: Yogyakarta and Sintang, West Kalimantan. This study used a comparative qualitative research design and applies content analysis to evaluate learning outcomes extracted from two English modules developed by teachers. Bloom's Revised Taxonomy was adopted as an analytical framework to classify learning outcomes into six cognitive levels and categorize them into LOTS and HOTS. The results show that the two modules cover all levels of Bloom's taxonomy, indicating broader compliance with the curriculum's emphasis on cognitive development. However, differences are often found in cognitive orientation. The module in Yogyakarta placed more emphasis on HOTS, targeting 56% LOTS and 44% HOTS, while the Sintang module emphasized LOTS more, targeting 54.5% LOTS and 45.5% HOTS. These differences reflected variations in regional context, teacher assessment, and resource availability in curriculum implementation. This study emphasizes the need for more authentic, balanced, and context-sensitive work guidelines to help integrate HOTS more consistently across regions within the Merdeka Curriculum framework.Keywords: Higher-Order Thinking Skills (HOTS); Learning Outcomes Alignment; Lower-Order Thinking Skills (LOTS); Merdeka Curriculum; Qualitative Content Analysis; Revised Bloom’s Taxonomy Framework